Reflections on the Legal Concept of Self-Employment in the Drafts of Labor Code - Gładoch, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The article concerns the projects of the labor code in the ﬁeld of forms of securing the self-employed. In 2006 and 2018 were created two projects of the Labor Code. The authors of them tried to protect self-employed persons in the best possible way. The ﬁrst Commission, which worked in the years 2002–2006, accepted in principle atypical forms of employment on the labor market. A completely diﬀerent view in this regard was presented by the Commission from 2016– 2018, which perceived employment outside the employment contract as a way of circumventing the provisions of labor law, a symptom of a pathology of the labor market. However, the forms of securing self-employed workers presented by both Committees are in fact very similar.